Sistem Informasi Data Keluarga (Siga) Berbasis Website Badan Kependudukan Dan Keluarga Berencana Nasional (BKKBN) Provinsi Sumatera Utara - Nurhidayah (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
In order to build a more 'qualified' data and information system, the BKKBN synchronizes the Indonesian Family Database (BDKI) with the population information system. The information system built by the BKKBN is packaged under the name of the Family Information System or SIGA. SIGA is used as a work map, program intervention and performance measurement. The implementation of SIGA will be piloted in 68 districts. SIGA is a very important 'vehicle' for BKKBN in particular. This is because family data and information serve as monitoring tools and the basis for planning, measuring performance and working maps at every level of the Family Planning and Family Development Population Program area in Indonesia.